2012
DOI: 10.1002/app.38075
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of residual stresses and distortion in carbon fiber‐epoxy composite parts due to curing process using finite element analysis

Abstract: To predict the final geometry of carbon fiber-epoxy composite parts, a methodology is introduced that takes into account cure kinetics, cure shrinkage, thermal strains, tool-part interface, and development of mechanical properties during cure. These parameters affect process-induced residual stresses and distortion in the parts. A module was developed for each mechanism and a fully 3D coupled thermomechanical finite element analysis was utilized. To validate the simulation results, a square composite panel was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Whereas, shrinkage is dependent on the physical properties of the components and their reactions, the creation of residual stresses within a composite are ultimately a function of the duration and temperature of the curing cycle [67,62]. The correlation between the appearance of high levels of residual stresses and the fatigue performance of composites (CFRPs) has been reported by many [86,87,68,88,89]. These researchers have found that the fatigue lifetime of CFRP decreases with a higher presence of residual strains within the composite.…”
Section: Effect Of Processing/manufacturing Defects On the Fatigue Prmentioning
confidence: 99%
“…Whereas, shrinkage is dependent on the physical properties of the components and their reactions, the creation of residual stresses within a composite are ultimately a function of the duration and temperature of the curing cycle [67,62]. The correlation between the appearance of high levels of residual stresses and the fatigue performance of composites (CFRPs) has been reported by many [86,87,68,88,89]. These researchers have found that the fatigue lifetime of CFRP decreases with a higher presence of residual strains within the composite.…”
Section: Effect Of Processing/manufacturing Defects On the Fatigue Prmentioning
confidence: 99%
“…Figure 18. Algorithm of the model developed by Rabearison et al [28] A methodology was introduced in the literature [61] to estimate dimensional distortion of a carbon fiber-epoxy composite part upon being removed from the tool. Different phenomena were taken into consideration in this estimation, including cure shrinkage, cure kinetics, tool-part interaction, thermal strains, and improvement of the mechanical properties during cure.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Simulation results were compared with the experimental data subsequently and a good agreement was observed. As explained before, the methodology was introduced in the previous study for flat panels [61] . Several…”
Section: Numerical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Residual thermal stresses (thermal forces and moments) arise in the fabrication of laminated and filament wound composites due to differences in CTE in matrix-dominated and fiber-dominated directions, however these affects are beyond the scope of the present investigation [49]. As residual stresses are not to be assessed, the nature of the fibre-matrix interface and the resulting thermal mismatch will not be assessed.…”
Section: High Temperature Effectsmentioning
confidence: 97%